2015
DOI: 10.1080/15533174.2014.988250
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Conductive PPy/Graphene/MnO2 Composite Using Ultrasonic Irradiation

Abstract: Highly conductive polypyrrole/graphene/manganese dioxide (PPy/graphene/MnO 2 ) composites are fabricated via ultrasonic irradiation using p-toluenesulfonic acid as a dopant. The microstructures of PPy/graphene/MnO 2 are evidenced by the SEM and TEM examinations. The effects of the graphene and MnO 2 loading on the electrical conductivity are investigated. The maximum conductivity of PPy/graphene/MnO 2 composites about 17.15 S/cm found with 3 wt.%graphene and 48.7 wt.% MnO 2 at room temperature. Such uniform st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Magnesium nitrate hexahydrate (MgNO 3 .6H 2 O) has been selected as the magnesium salt of choice for ionic conduction (Mg 2+ ) and MnO 2 as the inert ller for enhancing the conductivity properties for the preparation of chitosan biopolymer electrolytes in this work. MnO 2 one of the widely used metal oxides with very good physical and chemical properties has been used in variety of applications such as biosensors, biocatalysts and as electrodes in energy storage devices [21,22]. Yuhan Li et al studied the enhanced Li + ion transport (1.5 times higher) along with reinforced mechanical strength (2.3 times better tensile strength) upon the addition of ller MnO 2 nanosheet than the pure PEO lithium salt complexes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium nitrate hexahydrate (MgNO 3 .6H 2 O) has been selected as the magnesium salt of choice for ionic conduction (Mg 2+ ) and MnO 2 as the inert ller for enhancing the conductivity properties for the preparation of chitosan biopolymer electrolytes in this work. MnO 2 one of the widely used metal oxides with very good physical and chemical properties has been used in variety of applications such as biosensors, biocatalysts and as electrodes in energy storage devices [21,22]. Yuhan Li et al studied the enhanced Li + ion transport (1.5 times higher) along with reinforced mechanical strength (2.3 times better tensile strength) upon the addition of ller MnO 2 nanosheet than the pure PEO lithium salt complexes [23].…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial principium of polypyrrole is probably ascribed to seepage of cytoplasm since the mutual effect of bacteria cell membrane and the positive electrical charges in PPy chains. In addition, polypyrrole (PPy) is an organic semiconductor with a narrow band gap, strong electron transport capability and redox properties [30][31][32][33]. Therefore, PPy is widely used in the eld of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Another example for electrochemical full water splitting using solar energy was represented by Ali Han et al where they have shown a Janus-like Cu 3 P@NF electrode, and the catalytic current density of 10 mA/cm 2 was achieved at 1.7 V when potential was supplied using a solar cell . Overall, water splitting is a thermodynamically arduous reaction and demands enormously efficient and active electrode materials that considerably accelerate the sluggish kinetics of the two half-reactions ocurring simultaneously at both cathode (HER) and anode (OER). Electrocatalysts, the heart of an electrochemical water-splitting system, is preferred to be bifunctional in nature and has attracted immense amounts of research interest since a decade. There are two critical points that should be considered for the development of a water-splitting catalyst with respect to commercialization and industrial applications.…”
Section: Introductionmentioning
confidence: 99%